Strategic Development and Countermeasures for Shared Logistics Enterprises: Insights for Sports Industry Supply Chains Amid the Sino-US Trade War - Yaoyushan Zhang; Zhuolin Li; Ximei Huang; Ce Ding; Renjing Guo; Hongyuan Bi; Yiwen Zhang; Dongshu Cheng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In the context of the Sino-US trade war, shared logistics has emerged as a pivotal transformation and development direction with implications for global industries, including sports. This study explores the theoretical foundations of the sharing economy and shared logistics, analyzing the opportunities and challenges faced by China's logistics industry. The findings highlight persistent issues, such as reliance on single operational models and unaddressed technological bottlenecks, which impact the adaptability of shared logistics enterprises. These challenges are particularly relevant for the sports industry, where efficient logistics are critical for event management, equipment distribution, and supply chain optimization.Addressing the survival dilemmas faced by China's shared logistics enterprises, this research leverages a coupling driving mechanism, shared logistics experiments, and distribution systems. Through data analysis, an index system was established to evaluate the shared opportunities available to logistics enterprises. From the perspectives of operational management, financing channels, technological innovation, and collaborative networks, the study proposes a series of policy recommendations and strategic pathways for the development of shared logistics enterprises. The integration of shared logistics into the sports industry offers significant potential for streamlining operations, enhancing sustainability, and fostering global collaboration. These findings provide actionable insights for sports organizations seeking to build resilient supply chains, improve event logistics, and adapt to dynamic international trade conditions.